Clonality the genetics, ecology, and evolution of sexual abstinence in vertebrate animals - Avise, John C. (Oxford : Oxford University Press, 2008)
In this book, Avise describes the genetics, ecology, natural history, and evolution of the world's approximately 100 species of vertebrate animal that routinely display one form or another of clonal or quasi-clonal reproduction.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Vertebrates -- Reproduction; Reproduction, Asexual